Dedicated low-cost electronic ocarina for people with COPD: Rationale and prototype development. - Goncalves, Camila Siqueira Gouvea Acosta; Oliveira, Rafael Silva de; Reis, Stephany Almeida Rodrigues; Cunha, Andrielly da Silva; Hembecker, Paula Karina; Tsunoda, Audrey Tieko; Nohama, Percy (Nordic Journal of Music Therapy, 2025)
Introduction: Chronic obstructive pulmonary disease (COPD) is a condition characterized by airflow obstruction which can lead to physical and psychosocial challenges, with a higher prevalence in developing countries. Non-pharmacological interventions for this group of people include pulmonary rehabilitation as well as music interventions. Although music technology was recommended to adjust to the user's breathing capacity for music-making and to gather information about their performance, music therapy trials used acoustic wind instruments for their rehabilitation. This interdisciplinary project aims to develop a dedicated electronic wind instrument for people with COPD. Method: This project follows a systematic prototype methodology that includes product research, instrument development, and user validation. Based in Brazil, our team has decided on an electronic ocarina based on its cultural features, its popularity as a digital application, and its potential for respiratory training. Unlike existing technologies, the prototype intends to be dedicated and a low-cost solution. Results: The development process includes decision making about the appropriate mouthpiece, sensors, Arduino, pushbuttons, 3-D printing projects, building a MIDI interface and a dedicated software. This is an ongoing project, and our team is in the MIDI interface development stage. We aim to run the first hardware trial with users so that we can integrate their feedback into the functional prototype and the dedicated software for the following trials. Discussion: This project's strengths rely on the innovation of building viable electronic wind instruments that can facilitate self-management of people with COPD in developing countries, where access to healthcare can be challenging.